2020
DOI: 10.3390/ijerph17176101
|View full text |Cite
|
Sign up to set email alerts
|

Perceived and Real Aquatic Competence in Children from 6 to 10 Years Old

Abstract: This study aimed to analyze the relationship between perceived aquatic competence (PAC) and real aquatic competence (RAC) in 6 to 10 year old children in skills identified as relevant for surviving an aquatic accident. The study sample consisted of 105 children (8.2 + 1.3 years old). Two age groups were examined separately [G1, 6 to 7 years (n = 53); G2, 8 to 10 years (n = 52)]. Children’s aquatic competence was evaluated twice for skills linked to the risk of drowning: Firstly, using a common swimsuit (simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 43 publications
0
13
4
Order By: Relevance
“…Taking into account the score range of our perfectly aligned assessment tools (see Estevan & Barnett, 2018 for a discussion on the importance of aligning instruments), it can be suggested that these young children generally hold a fairly realistic estimate of their aquatic skills. Yet, our participants’ somewhat lower perceptions are in contrast to recent findings from Costa et al. (2020).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Taking into account the score range of our perfectly aligned assessment tools (see Estevan & Barnett, 2018 for a discussion on the importance of aligning instruments), it can be suggested that these young children generally hold a fairly realistic estimate of their aquatic skills. Yet, our participants’ somewhat lower perceptions are in contrast to recent findings from Costa et al. (2020).…”
Section: Discussioncontrasting
confidence: 99%
“…Despite the importance of accurate self-perception and parent-perception of a child’s aquatic skills, only limited research to date has focused on the relationship, and more importantly, the degree of (dis)agreement between these perceptions and children’s actual aquatic skill levels (e.g., Costa et al., 2020; De Pasquale et al., 2020). This limited research on aquatic skills is in stark contrast with the ever-increasing reports of actual and perceived motor competence on dry land (De Meester et al., 2020; Estevan & Barnett, 2018; Hulteen et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study highlights the need to educate children on the definitions and examples of differing PA intensities. Previous work has highlighted the difficulties children and adults have in understanding the differences between actual and perceived measures [ 3 , 4 ]. Although accelerometers are expensive and require technical expertise and additional software to analyse the data they collect effectively, they, along with other objective measures (pedometers or smart technology/smart watches), could help contribute to children’s awareness, knowledge and understanding of what they are doing [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…International research has indicated observing and understanding one’s own physical activity correctly is universally difficult for children [ 3 ]. This difficulty between PPA and APA has been identified in a variety of ways, most recently when young children are learning aquatic skills [ 4 ], as well as inconsistencies in their accuracy to estimate their ability to perform physical tasks [ 5 ].…”
Section: Introductionmentioning
confidence: 99%